Integrating Multimodality and Jigsaw Reading in Teaching Reading Comprehension to English Young Learners (A Case Study at Fifth Grade of Islamic Elementary School of Al Azhar 18 Cianjur) - Nia Kurniawati; Ai Komariah; Elis Homsini Maolida; Vina Aini Salsabila (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2018)
English young learners’ ability in reading comprehension is considerably below teachers’ expectation. Many students still rely on direct translation technique in comprehending reading text. Various techniques were developed to improve young learners reading comprehension such as jigsaw reading. However, teaching young learners need to involve all the senses as multimodality offers. The aims of the current study were (1) to gain some description on the process of integrating multimodality and jigsaw reading technique in teaching reading comprehension to young learners; (2) to examine the students’ response on the utilizing multimodality and jigsaw reading technique at a private elementary school; and (3) to find out the difficulties faced by the teacher in applying the technique. This research involved a class of five grader of Al Azhar 18 Islamic elementary school in Cianjur. It applied qualitative approach. The instruments used were observation sheet, interview, and document analysis. The results showed that there are three steps in applying the chosen technique including preparation, practice, and evaluation. The students’ response positively to the technique, since it gives them chance to work in a group and ask things they don’t know to their peer, and are very excited with different media provided by the teachers. As for the teachers, the difficulties are more related to the time constraints in preparing the materials that should be very vary and handling the grouping with diverse level of English among the young learners.Keywords: multimodalities, reading comprehension, action research, English for young learners